A participatory based public administration model to increase awareness and proactive behavior in occupational health and safety - Salamatul Afiyah (Universitas Aisyah Pringsewu, 2023)
Labor productivity is an important part of shaping a country's economy. Of course, the health and safety of workers is an important part of this productivity. Therefore, there needs to be a step to increase awareness in reducing the impact and risk of accidents. In the view of public administration, active participation by involving the community and stakeholders can help increase awareness of workplace safety. This study aims to be able to find a public administration model that is useful for increasing awareness of work safety. Qualitative methods will be used in this study using literature studies. The results of this study then found that through active participation, decision-making on occupational health and safety can increase awareness of risks and actions that need to be taken in the work environment. This can then create proactive work safety. Abstrak: Produktivitas tenaga kerja merupakan bagian penting dalam membentuk ekonomi suatu negara. Tentunya kesehatan dan keselamatan pekerja menjadi bagian penting dari produktivitas ini. Oleh karena itu, perlu adanya langkah untuk meningkatkan kesadaran dalam mengurangi dampak dan risiko kecelakaan. Dalam pandangan administrasi publik, partisipasi aktif dengan melibatkan masyarakat dan pemangku kepentingan dapat membantu meningkatkan kesadaran akan keselamatan kerja. Penelitian ini bertujuan untuk dapat menemukan model administrasi publik yang berguna untuk meningkatkan kesadaran keselamatan kerja. Metode kualitatif akan digunakan dalam penelitian ini dengan menggunakan studi literatur. Hasil penelitian ini kemudian menemukan bahwa melalui partisipasi aktif, pengambilan keputusan tentang kesehatan dan keselamatan kerja dapat meningkatkan kesadaran akan risiko dan tindakan yang perlu dilakukan di lingkungan kerja. Ini kemudian dapat menciptakan keselamatan kerja proaktif.